The Integration of Environmentally Friendly Fish Capture Technology for Fishermen in Padang City - Uzra, Murhenna; Febrianto, Iwan; Saputra, Roni; Edinov, Sanny; Sari, Siska Fitrima; Aryzegovina, Reffi; Yuliana, Liza; Sari, Mistia (The Future of Education Journal, 2025)
One part of the influence of technological developments is fishermen's fishing gear. The aim of using modern fishing gear is to make it easier for fishermen to reach a wider range of fishing activities and optimize their catch. However, not all fishing gear used by fishermen can have a positive effect on preserving the aquatic environment. Such as the use of trawl nets, chemicals and explosives can damage the potential of marine resources. It is necessary to understand and raise awareness among fishermen regarding the use of fishing gear that is not environmentally friendly. The Method for Conveying Understanding of the Integration of Environmentally Friendly Fishing Equipment Technology for Fishermen in the city of Padang is a form of Tridharma tertiary service for lecturers at Nahdlatul Ulama University, West Sumatra in creating resources that understand the sustainability of water potential so that they can be utilized sustainably for future generations. The results of this service activity motivate fishermen to work together to protect the aquatic environment by not using fishing gear that can damage the waters and have the potential to protect aquatic resources in the future.